2007
DOI: 10.1002/bem.20321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mobile phone electromagnetic fields on an auditory order threshold task

Abstract: The effect of acute exposure to radio frequency electromagnetic fields (RF EMF) generated by mobile phones on an auditory threshold task was investigated. 168 participants performed the task while exposed to RF EMF in one testing session (either global system for mobile communication (GSM) or unmodulated signals) while in a separate session participants were exposed to sham signals. Lateralization effects were tested by exposing participants either on the left side or on the right side of the head. No signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…These findings agree with recent double-blind studies that examined effects from RF-EMFs ranging from 385.25 MHz to 2100 MHz, which found that cognitive performance does not change as a consequence of exposure [Regel et al, 2006;Russo et al, 2006;Cinel et al, 2007Cinel et al, , 2008Haarala et al, 2007;Riddervold et al, 2008Riddervold et al, , 2010Unterlechner et al, 2008;Eltiti et al, 2009; Nieto-Hernandez et al, 2010]. We have found similar results with TETRA, using similar short-term and working memory tasks, as we have previously found with exposure to GSM and UMTS for both sensitives and controls [Eltiti et al, 2009].…”
Section: Cognitive Function and Physiological Response 33supporting
confidence: 92%
“…These findings agree with recent double-blind studies that examined effects from RF-EMFs ranging from 385.25 MHz to 2100 MHz, which found that cognitive performance does not change as a consequence of exposure [Regel et al, 2006;Russo et al, 2006;Cinel et al, 2007Cinel et al, , 2008Haarala et al, 2007;Riddervold et al, 2008Riddervold et al, , 2010Unterlechner et al, 2008;Eltiti et al, 2009; Nieto-Hernandez et al, 2010]. We have found similar results with TETRA, using similar short-term and working memory tasks, as we have previously found with exposure to GSM and UMTS for both sensitives and controls [Eltiti et al, 2009].…”
Section: Cognitive Function and Physiological Response 33supporting
confidence: 92%
“…The authors interpreted this finding as supporting their previous observations that pulse modulation of RF fields is necessary to induce changes in brain physiology. Cinel et al [2007] exposed 84 healthy volunteers to either an 888 MHz GSM signal or a CW signal. No effect was found on an auditory discrimination task from either signal type.…”
Section: Nervous System: Human Studiesmentioning
confidence: 99%
“…At perhaps the most basic level, auditory thresholds have not been consistently altered by MP exposure. For example, Maier et al (2004) reported performance decrements in an auditory threshold task after 50-minutes of MP-exposure, which was limited due to its small sample size (N=11), whereas Uloziene et al (2005), Parazzini et al (2007) and Cinel et al (2007) all failed to identify any MP effects on measures of auditory threshold. In terms of EEG measures of neural processes relating to audition, there is again no consistency.…”
Section: Introductionmentioning
confidence: 99%